STUDY OF TECHNOLOGICAL PROCESSES OF STAMPING OF FLANGETYPE PARTS BASED ON THE APPLICATION OF COMBINED EXPRESSION METHODS - MYHALEVICH, VOLODYMYR; KOLISNYK, MYKOLA; SHTUTS, ANDRII; HRYHORENKO, NAZAR (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The research of technological processes for stamping flange-type parts, particularly using combined extrusion methods, is a relevant direction in the field of materials science and mechanical engineering. Flanges, as structural elements, are widely used in various industries, especially in mechanical engineering, where high quality requirements are imposed. Ensuring high quality and cost-effectiveness in production necessitates the development of effective stamping technologies that achieve the required mechanical properties and accuracy of the parts. This paper examines the processes of combined extrusion, which integrate methods of bulk stamping and reverse extrusion. This approach allows for the simultaneous production of complex-shaped parts with enhanced accuracy and uniformity in the material structure. Such technologies ensure uniform deformation distribution and minimize the occurrence of defects, which is particularly important when manufacturing parts with high demands for reliability and durability. Special attention is given to the optimization of the stamping process parameters, including the selection of suitable materials, geometric parameters of the workpieces, and processing modes. The use of numerical modeling made it possible to investigate the influence of these parameters on the final properties of the parts, thereby reducing the number of experiments and shortening the development time of new technologies. Additionally, the paper addresses the energy consumption of the process, tool wear resistance, and the influence of different technological modes on the material’s microstructure. Thus, the research findings can be utilized to improve existing technologies and develop new methods for stamping flange-type parts, enhancing their market competitiveness and meeting the growing demands of modern production.